What job would you apply to? Findings on the impact of language on job searches - Ana Maria Diaz Escobar; Luz Magdalena Salas; Claudia Piras; Agustina Suaya (Inter-American Development Bank (IDB), 2023)
This study tests four "light touch" interventions in the language used in job posts of male- dominated occupations to attract female workers using a discrete choice experiment. This experiment had more than 5000 participants from five Latin American countries. We test two possible mechanisms: the gender-stereotypes related to job skills and the use of inclusive language. We find that language matters, and men and women value information and inclusive language in job advertisements. However, women are more sensitive in this regard. We test the effect of simply aggregating irrelevant, but additional words to the job ad, and find that when the inclusive language in the ad is subtle, the effect of having more words is very important. But it decreases when the language signals a strong preference for an inclusive work environment. These findings highlight the importance of language and the type of information presented in job advertisements in attracting a gender-balanced workforce.
Keywords: J16; J24; J63; C91; M54; 330; Language interventions; access to employment; labor discrimination; jobads; occupational segregation